Therapeutic Effects of the Combination of Alpha-Lipoic Acid (ALA) and Coenzyme Q10 (CoQ10) on Cisplatin-Induced Nephrotoxicity - Eman Aly Khalifa; Ahmed Nabil Ahmed; Khalid Shaaban Hashem; Ahmad Gad Allah (International Journal of Inflammation)
Background. Nephrotoxicity of cisplatin has been recognized since its introduction more than 25 years ago. However, despite intense efforts to develop less toxic and equally effective alternatives, cisplatin continues to be widely prescribed. Aim and Objectives. The study is aimed at assessing the possible prophylactic effect of coenzyme Q10 (CoQ10) and alpha-lipoic acid (ALA) (separately or in combination) on experimentally cisplatin-induced nephrotoxicity. Subjects and Methods. An experimental study was performed on adult male albino rats (n = 40), weighing 200–250 g. Rats were randomly divided into 5 groups: group I (normal saline control), group II (cisplatin control), group III (CoQ10 and cisplatin), group IV (ALA and cisplatin), and group V (CoQ10, ALA, and cisplatin). CoQ10 and/or ALA were given as pretreatment for 9 days, followed by cisplatin injection in the 10th day of the study, followed by a short posttreatment course for 3 days. Renal functions, tissue antioxidant activity, and inflammatory markers (tumor necrosis factor, TNF) were estimated along with histopathological study. Results. Renal function tests and urinary proteins were significantly higher within group II compared with other groups (P value <0.001). Creatinine clearance was significantly higher with combination therapy (group V compared to other groups). Both TNF and malondialdehyde (MDA) were significantly higher within group II whereas GSH content, catalase, and superoxide dismutase (SOD) were significantly lower in group II. MDA level was significantly lower when combination therapy was used. Marked renal damage was histologically detected in the cisplatin group, whereas the least renal damage was noticed in the combination group. Conclusion. The study confirmed the role of antioxidants in preventing nephrotoxicity caused by cisplatin; the prophylactic effect of combined therapy with CoQ10 and ALA is superior to that of monotherapy.